2017
DOI: 10.1097/aog.0000000000002316
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Morbidity and Maternal Complication Rates in Women With a Delivery Body Mass Index of 60 or Higher

Abstract: A BMI 60 or greater at the time of delivery is significantly associated with increased neonatal morbidity and increased maternal complication rates. In addition, neonatal morbidity and maternal complication rates with BMI 60 or greater were significantly higher when compared with women in any lesser obese BMI cohort between 30 and 59.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
1
17
1
2
Order By: Relevance
“…Their research clearly demonstrated a direct relationship between increasing BMI and higher risk of neonatal morbidity. More recently, Kim et al, 7 reported that women with a delivery BMI of 60 or higher display significantly higher neonatal morbidity than any other cohort of obese women with BMI between 30 and 59. The study was conducted at the University of Minnesota and the Hennepin County Medical Center in Minneapolis, Minnesota and included pertinent deliveries from January 2005 to April 2016.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their research clearly demonstrated a direct relationship between increasing BMI and higher risk of neonatal morbidity. More recently, Kim et al, 7 reported that women with a delivery BMI of 60 or higher display significantly higher neonatal morbidity than any other cohort of obese women with BMI between 30 and 59. The study was conducted at the University of Minnesota and the Hennepin County Medical Center in Minneapolis, Minnesota and included pertinent deliveries from January 2005 to April 2016.…”
mentioning
confidence: 99%
“…Over the years, research has demonstrated consistently that maternal obesity and overweight are associated with a higher risk of adverse pregnancy outcomes and higher rates of maternal, fetal, and neonatal morbidity. [6][7][8][9][10][11][12][13][14][15] Neonatal morbidity is generally defined as an increase in birth injuries, lower Apgar scores, respiratory distress syndrome, bacterial sepsis, hypoglycemia, neonatal seizures, NICU admissions, congenital anomalies, and even neonatal death. Morbidity risks are amplified by the degree of maternal obesity and women with a pre-pregnancy BMI outside the normal range are more likely to have infants who experience increased morbidity.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that infants delivered to women who enter pregnancy at a weight above normal (BMI of 25.0 or greater), are more likely to experience adverse health outcomes [2][3][4][5][6][7][8][9][10][11]. More specifically, it has been shown that a higher maternal BMI is directly linked to increased risks of neonatal morbidity [2][3][4]. The risks are considerable in obese women (BMI 30 or greater), but are most profound in women diagnosed with class III obesity (BMI 40 or greater).…”
mentioning
confidence: 99%
“…It is already known that pregnancies of normal weight and overweight women are associated with lower neonatal morbidity rates compared to women of class I, class II, and class III obesity [2][3][4][5][6][7][8][9][10][11]. In particular, a large retrospective study by Scott-Pillai, et al studying the impact of BMI on maternal and neonatal outcomes in 30,298 singleton pregnancies over an 8-year period in 2004-2011, clearly demonstrated that being overweight or obese increases the risk of adverse maternal and neonatal outcomes when compared to normal weight women [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation